Further Implications of Learning by Doing - Levhari, David (Review of Economic Studies, 1966)
Journal Article Further Implications of Learning by Doing Get access David Levhari David Levhari Hebrew University, Jerusalem Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 33, Issue 1, January 1966, Pages 31–38, https://doi.org/10.2307/2296638 Published: 01 January 1966